Friction material composition and friction material
Patent Information
- Application Number
- JP2023140319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明の一態様によれば、環境負荷の高い銅の含有量が銅元素として0.5質量%未満でありながら、高温域での高速制動時の効きおよび耐摩耗性に優れ、且つ常用の温度域においても十分な耐摩耗性を有し、さらに軽負荷制動時の錆落とし性に優れる摩擦材を提供することができる。
Smart Images

Figure 2025034131000001 
Figure 2025034131000002 
Figure 2025034131000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a friction material composition and a friction material. [Background technology]
[0002] Friction materials are used in the disc brake pads and brake shoes of braking devices such as disc brakes and drum brakes.
[0003] Patent Document 1 discloses a friction member having a friction material and a backing metal, in which the friction material does not contain copper, or if it contains copper, the copper content is less than 0.5 mass % in terms of elemental copper, and the friction material contains inorganic fibers having a fiber length of 400 μm or more.
[0004] Patent Document 2 discloses a friction material used for disc brake pads, which is formed from a friction material composition that does not contain a copper component, and which contains specific amounts of binders, organic fibers, metal sulfide-based lubricants, carbonaceous-based lubricants, titanates, wollastonite, particulate inorganic friction modifiers having a Mohs hardness of 4.5 or more and less than 8.0, inorganic friction modifiers having a Mohs hardness of less than 4.5, organic friction modifiers, and pH adjusters, and which does not contain any substances having a Mohs hardness of 8.0 or more, any metal element other than copper, or any alloy other than a copper alloy.
[0005] Patent Document 3 discloses a non-asbestos-based frictional material obtained by molding and curing a non-asbestos-based frictional material composition containing a fiber base material excluding asbestos, a binder, an organic filler, and an inorganic filler, the non-asbestos-based frictional material containing one or more inorganic substances selected from inorganic substances having a Mohs hardness of 4.5 or more and inorganic substances having a Mohs hardness of less than 4.5 and containing 50% by weight or more of components having a Mohs hardness of 4.5 or more as an abrasive, and the volume ratio of the total amount of organic substances to the total amount of abrasives in the composition (total amount of organic substances:total amount of abrasives) is 1.5:1 to 3.5:1. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2020 / 089979 [Patent Document 2] JP 2014-159871 A [Patent Document 3] JP 2002-241737 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the friction member described in Patent Document 1 is insufficient in terms of effectiveness and wear resistance during high-speed braking in high-temperature regions, and in wear resistance in normal temperature ranges such as when driving in urban areas. The friction material described in Patent Document 2 is insufficient in effectiveness during high-speed braking in high-temperature regions. The non-asbestos friction material described in Patent Document 3 is insufficient in removing rust generated on the contact surface with the friction counter-material such as the disc rotor or brake drum during light-load braking, and therefore is insufficient in terms of rust removal performance during light-load braking. Thus, there is room for improvement in the friction materials of the prior art.
[0008] An object of one aspect of the present invention is to provide a friction material that has excellent braking effectiveness and wear resistance during high-speed braking in a high-temperature range, and also has sufficient wear resistance in a normal temperature range, and further has excellent rust removal properties during light-load braking. [Means for solving the problem]
[0009] As a result of intensive research to solve the above-mentioned problems, the inventors have found for the first time that a friction material containing an inorganic material having a specific particle size and a specific Mohs hardness, monoclinic zirconium oxide, and magnesium hydroxide in specific amounts, in a friction material composition in which the copper content is less than 0.5 mass % in terms of elemental copper, has excellent effectiveness and wear resistance during high-speed braking in a high-temperature range, and also has sufficient wear resistance in a normal temperature range, and further has excellent rust removal properties during light-load braking, thereby completing the present invention. That is, a friction material composition according to one embodiment of the present invention is a friction material composition having a copper content of less than 0.5% by mass in terms of elemental copper, and the friction material composition contains, relative to the total amount of the friction material composition, 0.05% by mass or more and 1% by mass or less of one or two inorganic materials (excluding monoclinic zirconium oxide) selected from the group consisting of the following (1) and (2): (1) an inorganic material having an average particle size of 1 μm or less and a Mohs hardness of 7.5 or more and 8 or less; (2) an inorganic material having an average particle size of 50 μm or less and a Mohs hardness of 6 or more and less than 7.5, 5% by mass or more and 35% by mass or less of monoclinic zirconium oxide, and 0.5% by mass or more and 10% by mass or less of magnesium hydroxide. Effect of the Invention
[0010] According to one embodiment of the present invention, a friction material can be provided that has an environmentally hazardous copper content of less than 0.5 mass % in terms of elemental copper, yet has excellent braking effectiveness and wear resistance during high-speed braking at high temperatures, sufficient wear resistance even in the normal temperature range, and excellent rust removal properties during light-load braking. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <1.Friction material composition> A friction material composition according to one embodiment of the present invention is a friction material composition in which the copper content in the friction material composition is less than 0.5 mass % as copper element, and the friction material composition contains 0.05 mass % or more and 1 mass % or less of one or two inorganic materials (excluding monoclinic zirconium oxide) selected from the group consisting of the following (1) and (2) relative to the total amount of the friction material composition: (1) an inorganic material having a Mohs hardness of 7.5 or more and 8 or less and an average particle size of 1 μm or less; (2) an inorganic material having a Mohs hardness of 6 or more and less than 7.5 and an average particle size of 50 μm or less, monoclinic zirconium oxide in an amount of 5% by mass or more and 35% by mass or less, and magnesium hydroxide in an amount of 0.5 mass % or more and 10 mass % or less. The friction material composition according to one embodiment of the present invention is intended to be a composition in which friction material raw materials containing the above-mentioned components are blended. The friction material composition according to one embodiment of the present invention can be used to mold a friction material to be described later.
[0012] The friction material composition according to one embodiment of the present invention is environmentally friendly because the copper content in the friction material composition is less than 0.5 mass % in terms of copper element. Furthermore, since the friction material composition contains specific amounts of an inorganic material having a specific particle size and a specific Mohs hardness, monoclinic zirconium oxide, and magnesium hydroxide, the friction material composition has an excellent effect of providing a friction material that has excellent effectiveness and wear resistance during high-speed braking in a high-temperature range, sufficient wear resistance in a normal temperature range, and excellent rust removal properties during light-load braking, even though the copper content is less than 0.5 mass % in terms of copper element.
[0013] A friction material using the friction material composition according to one embodiment of the present invention has improved wear resistance during high-speed braking in a high-temperature range (e.g., 650°C or higher), and therefore can simultaneously achieve improved effectiveness during high-speed braking in a high-temperature range. In addition, improved wear resistance during high-speed braking in a high-temperature range can also be said to improve the strength of the friction material on the friction surface, which can be expected to improve the heat resistance of the friction material.
[0014] In addition, the friction material using the friction material composition according to one embodiment of the present invention can achieve both wear resistance during high-speed braking in a high-temperature range and wear resistance in a normal temperature range (for example, 100 to 200°C), and therefore has an excellent effect of having a longer life than conventional friction materials. Furthermore, the friction material using the friction material composition according to one embodiment of the present invention has excellent wear resistance, and therefore emits less dust due to wear. As a result, the wheels are less likely to be soiled by dust, and the amount of PM2.5 and PM10, which have a high environmental impact, is reduced.
[0015] In addition, the friction material using the friction material composition according to one embodiment of the present invention has excellent rust removal properties during light-load braking, so that rust generated on the surface of the friction counter-face material can be sufficiently removed even during light-load braking. Therefore, the friction material is less likely to adhere to the friction counter-face material due to rust generated on the contact surface with the friction counter-face material. As a result, there is an excellent effect that problems such as abnormal noise generation at the time of starting and surface peeling of the friction material are less likely to occur. Here, in this specification, "light-load braking" means a braking state in which the ratio of braking force obtained by friction (braking load) is lowered compared to conventional hydraulic brakes. More specifically, it means a state in which only friction occurs at a low speed where the initial speed of braking by friction is 10 km / hour (h) or less.
[0016] [Application] The friction material composition according to one embodiment of the present invention having the above-mentioned characteristics is particularly useful as a friction material composition for use in friction surfaces of disc brake pads and brake shoes for drum brakes in electric vehicles (EVs) and hybrid vehicles (HEVs). This is because EVs / HEVs are heavier than conventional gasoline vehicles due to the large batteries they are equipped with, and there is a tendency for regenerative braking and regenerative cooperative braking to contribute less to high-speed braking, so that the temperature of the brake pads or brake shoes is more likely to rise during high-speed braking in a high-temperature range than in conventional gasoline vehicles, and the frequency of reaching high temperatures increases.
[0017] Furthermore, in vehicles equipped with regenerative brakes or regenerative cooperative brakes, the ratio of braking force obtained by friction (braking load) decreases at medium to low speeds (20 to 60 km / h) where braking is frequently used in the market, resulting in a light load, compared to conventional hydraulic brakes. As a result, the rust removing power due to the braking load tends to be insufficient. The friction material composition according to one embodiment of the present invention is particularly useful in vehicles equipped with regenerative brakes or regenerative cooperative brakes, since it has excellent rust removing properties during light load braking.
[0018] The use of the friction material composition according to one embodiment of the present invention is not particularly limited to EV / HEV, and the composition can be suitably used as a friction material for friction surfaces such as disc brake pads and drum brake shoes employed in general vehicles including motorcycles.
[0019] [Raw materials] The raw materials (friction material raw materials) contained in the friction material composition according to one embodiment of the present invention will be described below.
[0020] (copper) The friction material composition according to one embodiment of the present invention has a copper content of less than 0.5 mass% in terms of copper element. The friction material composition according to one embodiment of the present invention has a very low content of copper and copper alloys, which are highly harmful to the environment, and therefore has the effect of providing an environmentally friendly friction material. From the viewpoint of providing a more environmentally friendly friction material, it is more preferable that the copper content in the friction material composition is 0 mass% (copper-free). The copper contained in the friction material composition according to one embodiment of the present invention may be derived from copper fibers added as a fiber substrate.
[0021] (Inorganic materials) A friction material composition according to one embodiment of the present invention contains, relative to 100% by mass of the friction material composition, 0.05% by mass or more and 1% by mass or less of one or two inorganic materials selected from the group consisting of the following (1) and (2) (excluding monoclinic zirconium oxide): (1) Inorganic materials with an average particle size of 1 μm or less and a Mohs hardness of 7.5 or more and 8 or less; (2) An inorganic material having an average particle size of 50 μm or less and a Mohs hardness of 6 or more and less than 7.5. Hereinafter, for convenience of explanation, "one or two inorganic materials selected from the group consisting of (1) and (2)" will be referred to as "inorganic material (A)", "(1) an inorganic material having an average particle size of 1 μm or less and a Mohs hardness of 7.5 or more and 8 or less" will be referred to as "inorganic material (1)", and "(2) an inorganic material having an average particle size of 50 μm or less and a Mohs hardness of 6 or more and less than 7.5" will be referred to as "inorganic material (2)". Note that "Mohs hardness" described in this specification means Mohs hardness expressed in 10 levels from 1 to 10. Mohs hardness can be measured according to a known measurement method. The inorganic particles may be added as an abrasive.
[0022] The inorganic material (A) may be only the inorganic material (1) or only the inorganic material (2). Also, it may be a combination of the inorganic material (1) and the inorganic material (2). For reasons described later, it is preferable to use the inorganic material (1) alone or the inorganic material (2) alone as the inorganic material (A). The reason is that when the inorganic material (1) and the inorganic material (2) are used in combination, the inorganic material (1) having a Mohs hardness of 7.5 or more and 8 or less scrapes and removes the inorganic material (2) having a Mohs hardness of 6 or more and less than 7.5, thereby losing the effect of the latter, and the same effect as when the inorganic material (1) is used alone is obtained. When inorganic material (1) and inorganic material (2) are used in combination, it is preferable to adjust the amounts of inorganic material (1) and inorganic material (2) so that the total content of inorganic material (1) and inorganic material (2) is 0.05 mass% or more and 1 mass% or less, and the content of inorganic material (1) alone is 0.05 mass% or more and 1 mass% or less, in order to fully obtain the effect of adding inorganic material (A).
[0023] (Inorganic materials (1)) The inorganic material (1) is particles of an inorganic material having an average particle size of 1 μm or less and a Mohs hardness of 7.5 or more and 8 or less, and is not monoclinic zirconium oxide.
[0024] The type of inorganic material having a Mohs hardness of 7.5 or more and 8 or less is not particularly limited. Examples of inorganic materials having such a Mohs hardness include zirconium silicate, beryl, and chromium oxide. The inorganic material (1) may be used alone or in combination of two or more types. From the viewpoints of availability and cost, the inorganic material (1) is preferably one or more types selected from the group consisting of zirconium silicate and chromium oxide.
[0025] (Inorganic materials (2)) The inorganic material (2) is particles of an inorganic material having an average particle size of 50 μm or less and a Mohs hardness of 6 or more and less than 7.5, and is not monoclinic zirconium oxide.
[0026] The type of inorganic material having a Mohs hardness of 6 or more and less than 7.5 is not particularly limited. Examples of inorganic materials having such a Mohs hardness include stabilized zirconium oxide, cerium oxide, silicon dioxide (including silica), magnesium oxide, alumina cement, cassiterite, orthoclase, and other minerals. Stabilized zirconium oxide refers to zirconium oxide stabilized in a cubic crystal at room temperature. The inorganic material (2) may be used alone or in combination of multiple types. From the viewpoints of availability and cost, the inorganic material (2) is preferably one or more types selected from the group consisting of stabilized zirconium oxide, cerium oxide, silicon dioxide, magnesium oxide, cassiterite, orthoclase, and other minerals.
[0027] (Actions and Effects of Inorganic Material (A)) (i) Improved rust removal during light-load braking Monoclinic zirconium oxide (details will be described later) is easily worn away, so the monoclinic zirconium oxide particles can spread over the friction surface even when braking under light load. Inorganic materials (1) and (2) have a hardness similar to that of monoclinic zirconium oxide, so they moderately grind the monoclinic zirconium oxide particles that have worn away and spread over the friction surface to make them sharp. The monoclinic zirconium oxide particles immediately after being worn away and spread over the friction surface have low sharpness and do not have the power to remove rust, but when they are ground to an acute angle by inorganic material (A), the monoclinic zirconium oxide particles can also contribute to removing rust. Inorganic material (A) also contributes to removing rust as an abrasive, but its rust removing ability during light load braking is insufficient. In addition to the rust removing effect of inorganic material (A), the large amount of monoclinic zirconium oxide with an acute angle removes rust under light load, improving rust removing ability during light load braking, and as a result, rust removing ability during light load braking is fully demonstrated.
[0028] The reason why the hardness of the inorganic material (A) is suitable for the above specific range is as follows. When the Mohs hardness of the inorganic material (A) is 6 or more, the effect of forming an acute angle by appropriately grinding the monoclinic zirconium oxide particles spread on the friction surface can be sufficiently obtained. Also, when the Mohs hardness of the inorganic material (A) is 8 or less, it is possible to prevent the monoclinic zirconium oxide spread on the friction surface from being completely ground and removed. Therefore, when the hardness of the inorganic material (A) is in the above range, it is possible to improve rust removal properties during light load braking.
[0029] Next, the reason why the suitable particle size differs depending on the hardness of the inorganic material (A) will be explained. First, as a premise, when the content (mass%) of the inorganic material (A) in the friction material composition is the same, the smaller the particle size of the inorganic material (A), the greater the number of particles present per unit area. Also, the greater the number of particles of the inorganic material (A) present per unit area, the more uniformly the monoclinic zirconium oxide particles spread over the friction surface can be scraped off.
[0030] The inorganic material (1) of the inorganic material (A) has a Mohs hardness of 7.5 or more and 8 or less, and is harder than monoclinic zirconium oxide. Therefore, the particles of the inorganic material (1) are less likely to become fine due to friction with the monoclinic zirconium oxide, and are less likely to spread on the friction surface. By making the average particle size of the particles of the inorganic material (1) 1 μm or less, the number of particles of the inorganic material (1) on the friction surface can be increased, and the monoclinic zirconium oxide that has worn away and spread on the friction surface can be more uniformly removed. As a result, the amount of acute-angled monoclinic zirconium oxide particles that can contribute to rust removal during light-load braking can be increased, and rust removal during light-load braking can be improved.
[0031] The inorganic material (2) among the inorganic materials (A) has a Mohs hardness of 6 or more but less than 7.5, which is equal to or less than that of monoclinic zirconium oxide. Therefore, the particles of the inorganic material (2) become finer due to friction with the monoclinic zirconium oxide that spreads on the friction surface due to wear at the beginning of braking, and can spread on the friction surface together with the monoclinic zirconium oxide. Therefore, from the viewpoint of the ease of spreading on the friction surface, the range of particle diameters that can obtain the effect of cutting the monoclinic zirconium oxide particles at an acute angle is wider than that of the inorganic material (1). In other words, even if the inorganic material (2) has an average particle size of more than 1 μm, the particles of the inorganic material (2) become finer due to friction with the monoclinic zirconium oxide, and can spread on the friction surface together with the monoclinic zirconium oxide, so that the effect of cutting the monoclinic zirconium oxide particles at an acute angle is sufficiently obtained.
[0032] In addition, as the particles of the inorganic material (2) become larger, the time required for the particles of the inorganic material (2) that have become finer due to friction with the monoclinic zirconium oxide to spread over the friction surface tends to increase. However, by setting the average particle size of the particles of the inorganic material (2) to 50 μm or less, the particles of the inorganic material (2) that have become finer due to friction with the monoclinic zirconium oxide can spread sufficiently over the friction surface even in regenerative braking or regenerative cooperative braking, which are used less frequently than conventional hydraulic brakes. As a result, the amount of acute-angled monoclinic zirconium oxide particles that can contribute to rust removal during light-load braking can be increased, and rust removal during light-load braking can be improved.
[0033] The average particle size of inorganic material (1) or (2) shall be the volume-based median size obtained by JIS Z 8825 "Particle size analysis - Laser analysis and scattering method." When checking the particle size of inorganic material (1) or (2) after the friction material is formed, the average particle size of particles corresponding to inorganic material (1) or (2) from an electron microscope image of the cross section of the friction material may be measured by measuring the volume-based particle size distribution by JIS Z 8827-1 "Particle size analysis - Image analysis method - Part 1: Static image analysis method," and then the median size may be obtained.
[0034] (ii) Improved wear resistance in the normal operating temperature range By adjusting the particle size and blending amount of the inorganic materials (1) and (2) having the specified Mohs hardness within the above-mentioned specific ranges, it is possible to maintain the wear resistance in the normal temperature range. The reason is as follows. Inorganic materials (1) and (2) are harder than cast iron and stainless steel, which are used as materials for disc rotors and brake drums. If the amount of inorganic materials (1) and (2) mixed exceeds 1% by mass, the amount of grinding of the disc rotor or brake drum increases rapidly, and the friction material is ground by the friction surface of the disc rotor or brake drum, which has been ground to an acute angle, so the amount of wear of the friction material increases significantly. If the amount of inorganic materials (1) and (2) mixed is 1% by mass or less, the amount of grinding of the disc rotor or brake drum is small, so that wear resistance in the normal temperature range can be maintained.
[0035] When the content of the inorganic material (A) in the friction material composition according to one embodiment of the present invention is 0.05% by mass or more based on 100% by mass of the friction material composition, the monoclinic zirconium oxide that has worn away and spread over the friction surface can be more uniformly scraped off, and the above-mentioned effect (i) is fully exhibited. Also, when the content of the inorganic material (A) in the friction material composition according to one embodiment of the present invention is 1% by mass or less based on 100% by mass of the friction material composition, sufficient wear resistance can be maintained in the normal temperature range.
[0036] (Monoclinic zirconium oxide) A friction material composition according to one embodiment of the present invention contains 5% by mass or more and 35% by mass or less of monoclinic zirconium oxide relative to 100% by mass of the friction material composition. Monoclinic zirconium oxide may be added as an inorganic filler. "Monoclinic zirconium oxide" refers to zirconium oxide whose crystal system is monoclinic. Zirconium oxide undergoes a crystal system transition depending on temperature. At room temperature (20°C), it is monoclinic, and as the temperature is increased, the crystal structure changes to tetragonal at 1170°C and to cubic at 2370°C. The phase transition is accompanied by a volume change.
[0037] Pure zirconium oxide is most stable at room temperature in the monoclinic system, but when fused with yttrium oxide or magnesium oxide, the cubic system becomes stable at room temperature. Zirconium oxide stabilized in the cubic system at room temperature is called "stabilized zirconium oxide".
[0038] Although monoclinic zirconium oxide has a Mohs hardness of 6 to 7, monoclinic zirconium oxide is distinguished from the above-mentioned inorganic material (A).
[0039] (Functions and Effects of Monoclinic Zirconium Oxide) (i) Improved rust removal during light-load braking Since monoclinic zirconium oxide is easily worn away, the monoclinic zirconium oxide particles can spread across the friction surface even under light-load braking. The monoclinic zirconium oxide particles that have worn away and spread across the friction surface are cut at acute angles by the inorganic material (A), allowing the monoclinic zirconium oxide particles to also contribute to rust removal. As a result, rust removal during light-load braking is improved.
[0040] (ii) Improved wear resistance in the normal operating temperature range Monoclinic zirconium oxide has lower toughness than stabilized zirconium oxide. Therefore, since monoclinic zirconium oxide has low grinding ability not only in the non-braking state but also in the braking state, the rotor grinding ability is low in both states, and the magnesium hydroxide spread on the friction surface is not easily lost. As a result, the rust prevention effect brought about by the magnesium hydroxide spread on the friction surface is fully exerted. In addition, since monoclinic zirconium oxide has lower toughness than stabilized zirconium oxide, the wear resistance of the pad is good.
[0041] (iii) Improved braking performance and wear resistance at high speeds in high temperature ranges Monoclinic zirconium oxide fuses with magnesium oxide (magnesium hydroxide in the friction material that has changed due to dehydration) due to the high heat generated by high-speed braking (high-load braking) in high-temperature ranges, becoming stabilized zirconium oxide. The stabilized zirconium oxide coating formed on the friction surface protects the friction surface. In addition, by reacting with magnesium oxide to become cubic stabilized zirconium oxide, volume change associated with phase transition does not occur, so the strength of the friction material on the friction surface is less likely to decrease. As a result, the wear resistance of the pad is improved, and the friction coefficient (μ) is also improved.
[0042] The thickness of the stabilized zirconium oxide coating formed on the friction surface varies depending on the content of monoclinic zirconium oxide in the friction material composition according to one embodiment of the present invention. When the content of monoclinic zirconium oxide in the friction material composition according to one embodiment of the present invention is 5% by mass or more relative to 100% by mass of the friction material composition, the stabilized zirconium oxide coating is formed with a sufficient thickness to realize the effect of (iii) above. When the content of monoclinic zirconium oxide in the friction material composition according to one embodiment of the present invention is 35% by mass or less relative to 100% by mass of the friction material composition, the stabilized zirconium oxide coating does not become too thick. As a result, magnesium hydroxide is not buried in the stabilized zirconium oxide coating, so that the rust resistance effect of magnesium hydroxide is fully realized. In addition, since the stabilized zirconium oxide coating is not easily peeled off from the friction surface, it is possible to prevent the friction area from becoming small due to the variation in coating thickness, and the effectiveness at high temperatures from decreasing. Therefore, the effect of (iii) above is fully realized.
[0043] (Grain size of monoclinic zirconium oxide) From the viewpoint of manifesting the above-mentioned effects (i) to (iii), the particle size of the monoclinic zirconium oxide is not particularly limited. Therefore, monoclinic zirconium oxide having a particle size that is usually adopted as an inorganic filler added to a friction material can be appropriately selected. From the viewpoint of handling during the production of the friction material composition, the average particle size of the monoclinic zirconium oxide is preferably 1 μm or more, more preferably 3 μm or more, more preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 10 μm or more. In addition, because it is possible to mix uniformly without bias during the production of the friction material composition and there is little influence on the deterioration of the wear resistance, the average particle size of the monoclinic zirconium oxide is preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 16 μm or less.
[0044] The average particle size of monoclinic zirconium oxide is the volume-based median size obtained by JIS Z 8825 "Particle size analysis - Laser analysis and scattering method." When checking the particle size of monoclinic zirconium oxide after the friction material is formed, the average particle size of particles corresponding to monoclinic zirconium oxide from an electron microscope image of the cross section of the friction material can be determined by measuring the volume-based particle size distribution by JIS Z 8827-1 "Particle size analysis - Image analysis method - Part 1: Static image analysis method," and then determining the median size.
[0045] (Magnesium hydroxide) The friction material composition according to one embodiment of the present invention contains, as one type of inorganic filler, 0.5% by mass or more and 10% by mass or less of magnesium hydroxide, based on 100% by mass of the friction material composition. The magnesium hydroxide may be added as an inorganic filler.
[0046] (Actions and Effects of Magnesium Hydroxide) (i) Improved rust removal during light-load braking Magnesium hydroxide is alkaline and has low solubility in water, so it is difficult to remove from the friction surface by water such as rain. This prevents the growth of strong rust on the friction surface, which contributes to improving rust removal under light loads.
[0047] (ii) Improved wear resistance in the normal operating temperature range Magnesium hydroxide has a Mohs hardness of 2 to 3 and is easily broken down by friction with friction-facing materials such as disc rotors and brake drums. Therefore, alkaline magnesium hydroxide spreads easily evenly on the friction surface. As a result, friction materials containing magnesium hydroxide have a high rust prevention effect.
[0048] In addition, magnesium hydroxide has a low solubility in water, so alkali is unlikely to disappear from the pad (friction surface, etc.) when it gets wet. For this reason, the rust-preventing effect lasts longer than other alkaline materials. As a result, friction materials containing magnesium hydroxide maintain their rust-preventing effect even when exposed to rain during the rainy season or when the pad is worn down.
[0049] The pH of magnesium hydroxide is 10.5, which is not high enough to promote the decomposition of the resin contained in the friction material as a binder. Therefore, friction materials containing magnesium hydroxide are less likely to lose strength due to the decomposition of the resin. As a result, the wear resistance of the pads is good. In addition, the rust-preventing effect of magnesium hydroxide suppresses rotor corrosion, so wear resistance can be maintained even after long-term use.
[0050] (iii) Improved braking performance and wear resistance at high speeds in high temperature ranges Magnesium hydroxide has a heat-resistant effect due to heat absorption by dehydration at 300 to 400°C. Magnesium hydroxide that spreads evenly on the friction surface changes to magnesium oxide by dehydration. Magnesium oxide fuses with monoclinic zirconium oxide (described later) due to the high heat generated by high-speed braking (high-load braking) in a high-temperature range, thereby contributing to the formation of a stabilized zirconium oxide coating. Stabilized zirconium oxide is easy to form a stable coating and has excellent heat resistance. The stabilized zirconium oxide coating improves wear resistance by protecting the friction surface, and therefore improves the friction coefficient (μ).
[0051] When the content of magnesium hydroxide in the friction material composition according to one embodiment of the present invention is 0.5% by mass or more relative to 100% by mass of the friction material composition, a sufficient amount of magnesium hydroxide spreads over the friction surface, and the above-mentioned effects (i) to (iii) are fully exhibited. When the content of magnesium hydroxide in the friction material composition according to one embodiment of the present invention is 10% by mass or less relative to 100% by mass of the friction material composition, the effect of volume change due to dehydration of magnesium hydroxide is small, and the strength of the base material of the friction material is unlikely to decrease. As a result, the wear resistance of the pad in the normal temperature range is good, and sufficient heat resistance effect is also obtained.
[0052] (magnesium hydroxide particle size) From the viewpoint of manifesting the above-mentioned effects (i) to (iii), the particle size of magnesium hydroxide is not particularly limited. Therefore, magnesium hydroxide having a particle size that is usually adopted as an inorganic filler to be added to a friction material can be appropriately selected. However, from the viewpoint of handling during the production of the friction material composition, the average particle size of magnesium hydroxide is preferably 2 μm or more, more preferably 4 μm or more. In addition, since it is possible to mix uniformly without bias during the production of the friction material composition, and since magnesium hydroxide particles are unlikely to fall off the friction surface during braking, the effect of improving the effectiveness and wear resistance during high-speed braking in a high-temperature range can be stably obtained at any place on the friction surface, the average particle size of magnesium hydroxide is preferably 20 μm or less, more preferably 15 μm or less.
[0053] The average particle size of magnesium hydroxide is the volume-based median size obtained by JIS Z 8825 "Particle size analysis - Laser analysis and scattering method." When checking the particle size of magnesium hydroxide after the friction material is formed, the average particle size of particles corresponding to magnesium hydroxide can be obtained from an electron microscope image of the cross section of the friction material by measuring the volume-based particle size distribution by JIS Z 8827-1 "Particle size analysis - Image analysis method - Part 1: Static image analysis method," and then the median size can be obtained.
[0054] (Preferable content of each component) From the viewpoint of further improving rust removability during light load braking, the content of the inorganic material (A) in the friction material composition is preferably 0.2 mass % or more and 1 mass % or less based on 100 mass % of the friction material composition.
[0055] From the viewpoint of further improving the effectiveness and wear resistance during high-speed braking in a high temperature range, the wear resistance in a normal temperature range, and the rust removability during light-load braking, the content of monoclinic zirconium oxide in the friction material composition is preferably 20 mass % or more and 30 mass % or less, relative to 100 mass % of the friction material composition.
[0056] From the viewpoint of further improving the effectiveness and wear resistance during high-speed braking in a high temperature range, the wear resistance in a normal temperature range, and the rust removability during light-load braking, the content of magnesium hydroxide in the friction material composition is preferably 1% by mass or more and 5% by mass or less, relative to 100% by mass of the friction material composition.
[0057] In the friction material composition according to one embodiment of the present invention, at least one of (a) the content of the inorganic material (A), (b) the content of the monoclinic zirconium oxide, and (c) the content of the magnesium hydroxide is preferably the above-mentioned preferred content. For example, only (a), only (b), or only (c) may be the above-mentioned preferred content. Alternatively, the combination of (a) and (b), the combination of (a) and (c), or the combination of (b) and (c) may be the above-mentioned preferred content. Alternatively, all of (a) to (c) may be the above-mentioned preferred content.
[0058] From the viewpoint of exhibiting a more preferable effect, in the friction material composition according to one embodiment of the present invention, the content of the inorganic material (A) in the friction material composition is more preferably 0.2% by mass or more and 1% by mass or less, the content of the monoclinic zirconium oxide in the friction material composition is more preferably 20% by mass or more and 30% by mass or less, and the content of the magnesium hydroxide in the friction material composition is more preferably 1% by mass or more and 5% by mass or less.
[0059] (Other Ingredients) The friction material composition according to one embodiment of the present invention may contain, in addition to the above-mentioned components, a fiber base material, a binder, an organic filler, and an inorganic filler different from monoclinic zirconium oxide and magnesium hydroxide as friction material raw materials, within a range that does not impair the effects of the present invention.
[0060] (metallic material) Examples of the metal material include metal fibers and metal powders. Examples of the metal fibers and powders include fibers and powders made of a single metal such as steel, stainless steel, aluminum, zinc, and tin, as well as fibers and powders made of the respective alloy metals. The metal material can be used alone or in combination with a plurality of types. Since the metal material is prone to adhesion to the disc rotor or drum brake, the content of the metal material in the friction material composition is preferably 1.2 mass% or less from the viewpoint of maintaining wear resistance in the normal temperature range.
[0061] (Textile base material) Examples of the fiber base material include organic fibers and inorganic fibers. These fibers may be natural fibers or synthetic fibers that are artificially synthesized. Examples of the organic fibers include aromatic polyamide fibers (aramid fibers), acrylic fibers, cellulose fibers, and carbon fibers. Examples of the inorganic fibers include rock wool and glass fibers. The above-mentioned metal fibers can also be defined as the fiber base material. The fiber base material can be used alone or in combination with a plurality of types. The content of the fiber base material in the friction material composition is not particularly limited, and can be the content that is usually adopted in the technical field.
[0062] (Binding material) The binder has a function of binding the friction material raw materials in the friction material composition. The binder is not particularly limited as long as it can exhibit the above-mentioned performance, and binders known in the technical field can be preferably used. Specific examples of the binder include resins such as phenolic resin, epoxy resin, melamine resin, and imide resin. The binder can be used alone or in combination of two or more types. The content of the binder in the friction material composition is not particularly limited, and can be the content normally adopted in the technical field. The binder may also contain modified components such as silicone rubber, acrylic rubber, and cashew oil.
[0063] (organic filler) The organic filler has a function as a friction modifier for improving wear resistance and the like. The organic filler is not particularly limited as long as it can exhibit the above-mentioned performance, and organic fillers known in the technical field can be preferably used. Specific examples of the organic filler include rubber powder, tire powder, cashew dust, fluororesin, melamine cyanurate, and polyethylene resin. The organic filler can be used alone or in combination of two or more types. The organic filler may be surface-coated with phosphoric acid or fluororesin. The content of the organic filler in the friction material composition is not particularly limited, and can be the content normally adopted in the technical field.
[0064] (Another inorganic filler different from monoclinic zirconium oxide and magnesium hydroxide) The friction material composition according to one embodiment of the present invention may contain another inorganic filler different from monoclinic zirconium oxide and magnesium hydroxide, as long as the effect of the present invention is not impaired. The other inorganic filler different from monoclinic zirconium oxide and magnesium hydroxide is preferably an inorganic material having a Mohs hardness of less than 6. As such an inorganic material, inorganic materials known in the art can be preferably used, and examples thereof include barium sulfate, mica, iron oxide (ferrous oxide, ferric oxide, etc.), titanates, calcium hydroxide, etc. Examples of titanates include alkali metal titanates, alkali metal titanates, group II salts, etc., and specific examples thereof include potassium titanate, sodium titanate, lithium titanate, lithium potassium titanate, magnesium potassium titanate, etc. These inorganic fillers can be used alone or in combination. The content of the inorganic filler other than monoclinic zirconium oxide and magnesium hydroxide in the friction material composition is not particularly limited, and may be appropriately adjusted so that the total content of the inorganic filler combined with the monoclinic zirconium oxide and magnesium hydroxide falls within the range of the inorganic filler content adopted in the technical field.
[0065] By including titanate as an inorganic filler different from monoclinic zirconium oxide and magnesium hydroxide, the coating formed on the friction surface during high-speed braking in a temperature range of 650°C or higher becomes stronger, and the heat resistance (effectiveness and wear resistance) of the friction material is further improved, which is preferable. In this case, the upper limit of the content of titanate is not particularly limited, and it may be appropriately adjusted so that the total content of the inorganic filler combined with monoclinic zirconium oxide and magnesium hydroxide is the content of the inorganic filler adopted in the technical field. The higher the content of titanate, the more the heat resistance of the friction material described above is improved, which is preferable.
[0066] Furthermore, the particle size of the inorganic filler other than monoclinic zirconium oxide and magnesium hydroxide is not particularly limited, and inorganic materials having an average particle size usually adopted in the art can be preferably used.
[0067] (Lubricant) The friction material composition according to one embodiment of the present invention may further contain a lubricant within a range that does not impair the effects of the present invention. The lubricant is not particularly limited, and lubricants known in the art can be preferably used. Specific examples of the lubricant include coke, graphite, carbon black, graphite, and metal sulfides. Examples of the metal sulfide include tin sulfide, antimony trisulfide, molybdenum disulfide, bismuth sulfide, iron sulfide, zinc sulfide, and tungsten sulfide. These lubricants can be used alone or in combination. The content of the lubricant is not particularly limited, and can be the content normally adopted in the art.
[0068] The friction material composition according to one embodiment of the present invention may contain an inorganic material having a Mohs hardness of greater than 8 as long as the effect of the present invention is not impaired. However, from the viewpoint of achieving a preferable effect, it is preferable that the friction material composition does not contain an inorganic material having a Mohs hardness of greater than 8.
[0069] (Method of manufacturing friction material composition) The friction material composition according to one embodiment of the present invention can be manufactured by a manufacturing method including a mixing step of blending the above-mentioned friction material raw materials and mixing them. From the viewpoint of uniformly mixing the friction material raw materials, the mixing step is preferably a step of mixing powder-like friction material raw materials. The mixing method and mixing conditions in the mixing step are not particularly limited as long as the friction material raw materials can be uniformly mixed, and methods known in the art can be adopted. For example, the friction material raw materials may be mixed at room temperature for about 10 minutes using a known mixer such as a Fenchel mixer or a Loedige mixer. In the mixing step, the mixture of friction material raw materials may be mixed while being cooled by a known cooling method so that the temperature of the friction material raw materials does not increase during mixing.
[0070] <2.Friction material> The friction material according to one aspect of the present invention is obtained by molding the friction material composition according to one aspect of the present invention. The friction material composition according to one aspect of the present invention in the friction material according to one aspect of the present invention has already been described, and therefore will not be described again here.
[0071] (Method of manufacturing friction material) The friction material according to one embodiment of the present invention can be manufactured by a manufacturing method including a molding step of molding the friction material composition according to one embodiment of the present invention. The molding method and molding conditions in the molding step are not particularly limited as long as the friction material composition according to one embodiment of the present invention can be molded into a predetermined shape, and methods known in the art can be adopted. For example, the friction material composition according to one embodiment of the present invention can be molded by pressing with a press or the like. As a molding method by pressing, either a hot press method in which the friction material composition according to one embodiment of the present invention is heated and pressed to mold, or a room temperature press method in which the friction material composition according to one embodiment of the present invention is pressed and molded at room temperature without heating, can be suitably adopted. When molding by the hot press method, for example, the friction material composition according to one embodiment of the present invention can be molded into a friction material by setting the molding temperature to 140° C. or more and 200° C. or less (preferably 160° C.), the molding pressure to 10 MPa or more and 40 MPa or less (preferably 20 MPa), and the molding time to 3 minutes or more and 15 minutes or less (preferably 10 minutes). In the case of molding by a room temperature pressing method, for example, the friction material composition according to one embodiment of the present invention can be molded into a friction material by setting the molding pressure to 50 MPa or more and 200 MPa or less (preferably 100 MPa) and the molding time to 5 seconds or more and 60 seconds or less (preferably 15 seconds). Furthermore, if necessary, a polishing step may be performed in which the surface of the friction material is polished to form a friction surface.
[0072] <3. Friction materials> The present invention also includes a friction member using the friction material according to an embodiment of the present invention as a friction surface. The friction member may be configured to include only the friction material according to an embodiment of the present invention, or may be configured to integrate the friction material according to an embodiment of the present invention with a plate-shaped member such as a metal plate as a back plate. The friction material according to an embodiment of the present invention in the friction member according to an embodiment of the present invention has already been described, and therefore will not be described again here.
[0073] When the friction member according to an embodiment of the present invention is configured by integrating the friction material according to an embodiment of the present invention with a plate-shaped member, the friction material according to an embodiment of the present invention and the plate-shaped member can be bonded to each other by clamping the friction material according to an embodiment of the present invention and the plate-shaped member, and then heat-treating the friction material according to an embodiment of the present invention. The conditions of the clamping treatment are not particularly limited, but are, for example, 180°C, 1 MPa, and 10 minutes. The conditions of the heat treatment after the clamping treatment are also not particularly limited, but are, for example, 150°C or higher and 250°C or lower, 5 minutes or higher, and 180 minutes or lower, and are preferably 230°C and 3 hours.
[0074] 〔summary〕 [1] A friction material composition according to a first aspect of the present invention is a friction material composition having a copper content of less than 0.5 mass % in terms of elemental copper, The friction material composition contains one or two inorganic materials selected from the group consisting of the following (1) and (2) (excluding monoclinic zirconium oxide) in an amount of 0.05% by mass or more and 1% by mass or less based on the total amount of the friction material composition: (1) Inorganic materials with an average particle size of 1 μm or less and a Mohs hardness of 7.5 or more and 8 or less; (2) Inorganic materials with an average particle size of 50 μm or less and a Mohs hardness of 6 or more and less than 7.5; Monoclinic zirconium oxide is 5% by mass or more and 35% by mass or less, and Magnesium hydroxide: 0.5% by mass or more and 10% by mass or less; include.
[0075] According to this configuration, while the copper content is less than 0.5% by mass in terms of copper element, compared with conventional friction materials, it is possible to provide a friction material that is superior in effectiveness and wear resistance during high-speed braking in high-temperature ranges, has sufficient wear resistance even in the normal temperature range, and further has excellent rust removal properties during light-load braking.
[0076] [2] In the friction material composition according to the second aspect of the present invention, in the friction material composition according to the first aspect, the content of one or two kinds of inorganic materials selected from the group consisting of (1) and (2) in the friction material composition is preferably 0.2% by mass or more and 1% by mass or less.
[0077] This configuration has the effect of further improving rust removal properties during light load braking.
[0078] [3] In the friction material composition according to the third aspect of the present invention, in the first or second aspect, the content of the monoclinic zirconium oxide in the friction material composition is preferably 20% by mass or more and 30% by mass or less.
[0079] Such a configuration has the effect of further improving the braking effectiveness and wear resistance during high speed braking in high temperature ranges, the wear resistance in the normal temperature range, and the rust removal properties during light load braking.
[0080] [4] In the friction material composition according to Aspect 4 of the present invention, in any one of Aspects 1 to 3, the content of the magnesium hydroxide in the friction material composition is preferably 1 mass % or more and 5 mass % or less.
[0081] Such a configuration has the effect of further improving the braking effectiveness and wear resistance during high speed braking in high temperature ranges, the wear resistance in the normal temperature range, and the rust removal properties during light load braking.
[0082] [5] A friction material composition according to a fifth aspect of the present invention is the friction material composition according to the first aspect, wherein the content of one or two inorganic materials selected from the group consisting of (1) and (2) in the friction material composition is 0.2% by mass or more and 1% by mass or less, the content of the monoclinic zirconium oxide in the friction material composition is 20% by mass or more and 30% by mass or less, and the content of the magnesium hydroxide in the friction material composition is 1% by mass or more and 5% by mass or less.
[0083] Such a configuration has the effect of further improving the braking effectiveness and wear resistance during high speed braking in high temperature ranges, wear resistance in the normal temperature range, and rust removal properties during light load braking.
[0084] [6] A friction material according to a sixth aspect of the present invention is formed by molding the friction material composition according to any one of the first to fifth aspects.
[0085] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in each embodiment are also included in the technical scope of the present invention. EXAMPLES
[0086] <Friction material raw materials> The main friction material raw materials used in the examples and comparative examples are as follows:
[0087] Alumina: average particle size 0.7μm, Mohs hardness 9 Zirconium silicate: average particle size 0.8μm or 19μm, Mohs hardness 7.5 Stabilized zirconium oxide: average particle size 35μm, Mohs hardness 7 Mineral (cassiterite): average grain size 190μm, Mohs hardness 6.5 Monoclinic zirconium oxide: average grain size 10μm or more, Mohs hardness 7 Magnesium hydroxide: average particle size 4μm, Mohs hardness 2 Titanate: Mohs hardness 4 Barium sulfate: Mohs hardness 3 Mica: Mohs hardness 3 Iron oxide: Mohs hardness 5 Calcium hydroxide: Mohs hardness 2 Iron fibre: Mohs hardness 4
[0088] Among these raw materials, inorganic material particles with a Mohs hardness of 6 or more, excluding monoclinic zirconium oxide, i.e., alumina, zirconium silicate, stabilized zirconium oxide, and mineral particles, were added as abrasives. Alumina particles with an average particle size of 0.7 μm and a Mohs hardness of 9, and zirconium silicate particles with an average particle size of 0.8 μm and a Mohs hardness of 7.5 correspond to inorganic material (1). Stabilized zirconium oxide particles with an average particle size of 35 μm and a Mohs hardness of 7 correspond to inorganic material (2).
[0089] Also, particles of inorganic materials having a Mohs hardness of less than 6, namely, particles of titanate, barium sulfate, mica, iron oxide, calcium hydroxide, and magnesium hydroxide, were added as inorganic fillers.
[0090] Raw materials other than the above-mentioned friction raw materials were those commonly used in the art.
[0091] Example 1 <Brake pad manufacturing> The raw materials were mixed according to the mixing ratio shown in Table 1, and mixed for about 10 minutes at room temperature (20°C) using a Loedige mixer to obtain a friction material composition. The blending amount of each raw material in Table 1 is expressed in mass% of the friction material composition. A blank space in the table indicates that the component was not added.
[0092] The friction material composition was heated and compressed by a hot press method using a molding press to obtain a molded product. The molding conditions for the hot press method were as follows: Molding temperature: 160℃ Molding pressure: 20MPa Moulding time: 10 minutes.
[0093] The surface of the obtained molded product was polished with a polishing machine to form a friction surface, and a friction material was obtained. The brake pad of Example 1 was produced using this friction material, and a high-temperature test and a running simulation test were performed. The brake pad produced in Example 1 had a friction material thickness of 12.5 mm and a friction material projected area of 55 cm2. 2 It was.
[0094] [Examples 2 to 16] Brake pads of Examples 2 to 8 were produced in the same manner as Example 1, except that the raw materials were mixed according to the mixing ratio shown in Table 1. Brake pads of Examples 9 to 16 were produced in the same manner as Example 1, except that the raw materials were mixed according to the mixing ratio shown in Table 2.
[0095] [Comparative Examples 1 to 16] Brake pads of Comparative Examples 1 to 8 were produced in the same manner as in Example 1, except that the raw materials were blended according to the blending ratios shown in Table 3. Brake pads of Comparative Examples 9 to 16 were produced in the same manner as in Example 1, except that the raw materials were blended according to the blending ratios shown in Table 4.
[0096] <High temperature test> An AMS fade test (evaluation conditions published in the German automobile magazine Auto Motor und Sport: vehicle speed 130 km / h, maximum rotor temperature 650°C or higher) was carried out, and the following evaluations were made for the brake pads of Examples 1 to 16 and Comparative Examples 1 to 16. The maximum rotor temperature in each test was 650 to 670°C.
[0097] (Minimum friction coefficient) The lowest coefficient of friction during the AMS fade test was measured by the following method.
[0098] (Method of measuring minimum friction coefficient) Using the minimum torque during one braking, the friction coefficient for each braking was calculated using the formula described in JIS D 0106. The lowest friction coefficient during the test was taken as the minimum friction coefficient.
[0099] The measurement results of the minimum friction coefficient were evaluated using a five-level score of 1 to 5 according to the following criteria. 5: More than 20% improvement over Comparative Example 1 4: Improved by 10% or more and 20% or less compared to Comparative Example 1 3: Same or equivalent to Comparative Example 1 2: 10% or more and 20% or less worse than Comparative Example 1 1: Deterioration of more than 20% compared to Comparative Example 1 Here, the minimum friction coefficient of the brake pad to be evaluated was evaluated as "improved" if it increased by 10% or more compared to the minimum friction coefficient of the brake pad of Comparative Example 1, and was evaluated as "deteriorated" if it decreased by 10% or more compared to the minimum friction coefficient of the brake pad of Comparative Example 1. If the increase or decrease in the minimum friction coefficient of the brake pad to be evaluated was less than 10% compared to the minimum friction coefficient of the brake pad of Comparative Example 1, it was evaluated as the same or equivalent to Comparative Example 1.
[0100] (Wear amount) The amount of wear of the brake pads after the AMS fade test was measured by the following method.
[0101] (Method of measuring wear amount) The amount of wear was measured according to JASO C427 6. Measurement method.
[0102] After the test, the amount of pad wear was measured at eight points on each brake pad, and the average value was taken as the "average pad wear amount."
[0103] The measurement results of the amount of wear were evaluated using a five-level score of 1 to 5 according to the following criteria. 5: More than 20% improvement over Comparative Example 1 4: Improved by 10% or more and 20% or less compared to Comparative Example 1 3: Same or equivalent to Comparative Example 1 2: 10% or more and 20% or less worse than Comparative Example 1 1: Deterioration of more than 20% compared to Comparative Example 1 Here, the brake pads to be evaluated were evaluated as "improved" if their average wear volume decreased by 10% or more compared to the average wear volume of the brake pads of Comparative Example 1, and were evaluated as "worsened" if their average wear volume increased by 10% or more compared to the average wear volume of the brake pads of Comparative Example 1. If the increase or decrease in the average wear volume of the brake pads to be evaluated was less than 10% compared to the average wear volume of the brake pads of Comparative Example 1, the brake pads to be evaluated were evaluated as the same or equivalent to Comparative Example 1.
[0104] <Driving simulation wear test> A test (commonly known as the LACT simulation test) was conducted using a bench tester simulating urban driving in Los Angeles (LA), and the estimated lifespan (estimated pad lifespan) (miles) of the brake pads of Examples 1 to 16 and Comparative Examples 1 to 16 were calculated using the following formula (1). Estimated pad life (miles) = pad thickness (mm) ÷ average pad wear (mm) × test mileage (miles) (1) Here, "pad thickness (mm)" is the thickness of the brake pad before the LACT simulation test, and "average pad wear (mm)" is the average wear of the brake pad before the LACT simulation test, and the measurement method conforms to JASO C427 6. Measurement method. The average rotor temperature in the running simulation wear test was 100 to 200°C.
[0105] The calculation results of the estimated pad life were evaluated using a five-level score from 1 to 5 according to the criteria shown below. 5: More than 20% improvement over Comparative Example 1 4: Improved by 10% or more and 20% or less compared to Comparative Example 1 3: Same or equivalent to Comparative Example 1 2: 10% or more and 20% or less worse than Comparative Example 1 1: Deterioration of more than 20% compared to Comparative Example 1 Here, if the estimated pad life of the brake pad to be evaluated increased by 10% or more compared to the estimated pad life of the brake pad of Comparative Example 1, it was evaluated as "improved," and if the estimated pad life of the brake pad to be evaluated decreased by 10% or more compared to the estimated pad life of the brake pad of Comparative Example 1, it was evaluated as "deteriorated." If the increase or decrease in the estimated pad life of the brake pad to be evaluated was less than 10% compared to the estimated pad life of the brake pad of Comparative Example 1, it was evaluated as the same or equivalent to Comparative Example 1.
[0106] <Light-load rust removal test> The light load rust removal properties of the brake pads of Examples 1 to 16 and Comparative Examples 1 to 16 were evaluated using a bench tester. Regenerative braking and regenerative cooperative braking were simulated, and braking by friction braking was started at 10 km / hour (h). Braking initial speed: 10km / hour (h) Braking final speed: 0km / hour (h) Deceleration: 0.8m / s 2
[0107] The rust removal rate was calculated using the following formula (2). Rust removal rate (%) = (rust thickness of disc rotor before braking - rust thickness of disc rotor after 100 brakings) ÷ rust thickness of disc rotor before braking × 100 (2) Here, the "rust thickness of the disc rotor before braking" was calculated using the following formula (3). Rust thickness of disc rotor before braking = Thickness of disc rotor after rust occurs - Thickness of disc rotor before rust occurs (3) The thickness of the disk rotor was measured at multiple points near the center of the sliding surface using a micrometer, and the average value was used.
[0108] In this test, a disc rotor with 50 μm of rust was used, so the "rust thickness on the disc rotor before braking" was 50 μm.
[0109] Based on the calculation results of the rust removal rate, the rust removability under light load was evaluated with a 5-level score of 1 to 5 according to the following criteria. 5: More than 20% improvement over Comparative Example 1 4: Improved by 10% or more and 20% or less compared to Comparative Example 1 3: Same or equivalent to Comparative Example 1 2: 10% or more and 20% or less worse than Comparative Example 1 1: Deterioration of more than 20% compared to Comparative Example 1 Here, if the rust removal rate of the brake pad to be evaluated increased by 10% or more compared to the rust removal rate of the brake pad of Comparative Example 1, it was evaluated as "improved," and if the rust removal rate of the brake pad to be evaluated decreased by 10% or more compared to the rust removal rate of the brake pad of Comparative Example 1, it was evaluated as "worsened." If the increase or decrease in the rust removal rate of the brake pad to be evaluated was less than 10% compared to the rust removal rate of the brake pad of Comparative Example 1, it was evaluated as the same or equivalent to Comparative Example 1.
[0110] <Result> The evaluation results of the high-speed test, the running simulation abrasion test, and the light-load rust removal test are shown in Tables 1 to 4. [Table 1]
[0111] [Table 2]
[0112] [Table 3]
[0113] [Table 4] As shown in Tables 1 and 2, the brake pads of Examples 1 to 16 contain specific amounts of an inorganic material having a specific particle size and a specific Mohs hardness, monoclinic zirconium oxide, and magnesium hydroxide, and as a result, compared to the brake pad of Comparative Example 1, it was confirmed that the brake pads have superior effectiveness and wear resistance during high-speed braking at high temperatures, have sufficient wear resistance even in the normal temperature range, and also have excellent rust removal properties during light-load braking.
[0114] In particular, a comparison of Examples 1 to 16 with Comparative Example 4 (not containing inorganic material (A)), Comparative Example 7 (not containing magnesium hydroxide) and Comparative Example 13 (not containing magnesium hydroxide) confirmed that the brake pads of Examples 1 to 16 exhibited a synergistic effect due to the combination of inorganic material (A) having a specific particle size and specific Mohs hardness, monoclinic zirconium oxide and magnesium hydroxide.
[0115] In addition, from the results of the examples and comparative examples, it was confirmed that, if the content of the inorganic material (A) is the same, the larger the particle size of the inorganic material (A), the less the light-load rust-removal property tends to be obtained. In addition, it was confirmed that, if the content of the inorganic material (A) increases, the light-load rust-removal property tends to improve, but on the other hand, the wear resistance in the normal temperature range tends to deteriorate. In the brake pads of Examples 1 to 16, the inorganic material (A) having a specific particle size and a specific Mohs hardness is selected and combined with monoclinic zirconium oxide and magnesium hydroxide, so that the light-load rust-removal property can be sufficiently improved with a small amount of inorganic material (A) added. Therefore, it was considered that the brake pads of Examples 1 to 16 can maintain sufficient wear resistance in the normal temperature range while sufficiently improving the light-load rust-removal property. [Industrial Applicability]
[0116] The friction material composition and friction material according to one embodiment of the present invention can be suitably used as friction members in braking systems of vehicles such as automobiles.
Claims
1. The friction material composition has a copper content of less than 0.5% by mass in terms of elemental copper, With respect to the total amount of the friction material composition, One or two inorganic materials selected from the group consisting of the following (1) and (2) (excluding monoclinic zirconium oxide) are contained in an amount of 0.05% by mass or more and 1% by mass or less: (1) an inorganic material having an average particle size of 1 μm or less and a Mohs hardness of 7.5 or more and 8 or less; (2) an inorganic material having an average particle size of 50 μm or less and a Mohs hardness of 6 or more and less than 7.5; Monoclinic zirconium oxide is 5% by mass or more and 35% by mass or less, and Magnesium hydroxide: 0.5% by mass or more and 10% by mass or less; A friction material composition comprising:
2. 2. The friction material composition according to claim 1, wherein the content of the one or two inorganic materials selected from the group consisting of (1) and (2) in the friction material composition is 0.2 mass % or more and 1 mass % or less.
3. 2. The friction material composition according to claim 1, wherein the content of the monoclinic zirconium oxide in the friction material composition is 20% by mass or more and 30% by mass or less.
4. The friction material composition according to claim 1 , wherein the content of the magnesium hydroxide in the friction material composition is 1% by mass or more and 5% by mass or less.
5. The content of one or two inorganic materials selected from the group consisting of (1) and (2) in the friction material composition is 0.2 mass% or more and 1 mass% or less, The content of the monoclinic zirconium oxide in the friction material composition is 20% by mass or more and 30% by mass or less, and The friction material composition according to claim 1 , wherein the content of the magnesium hydroxide in the friction material composition is 1% by mass or more and 5% by mass or less.
6. A friction material obtained by molding the friction material composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Non-asbestos-based friction material
JP2002241737A
Friction material
JP2014159871A
Friction member, composition for friction material, friction material, and vehicle
WO2020089979A1